Ada Apa dengan Dewan Pengawas Syariah di Koperasi Simpan Pinjam dan Pembiayaan Syariah? - Absor, Choirul; Hana, Kharis Fadlullah; Nur, Fatikha Rizqya (MALIA: Journal of Islamic Banking and Finance, 2019)
This study aims to determine the role of the Sharia Supervisory Board in supervising Sharia Savings and Loan Cooperatives (KSPPS) so that operations do not come out of sharia provisions. Sharia Supervisory Board includes legal assistants who have the duty to ensure and conduct supervision so that Sharia Financial Institutions are in sharia provisions. Savings and Loan Cooperatives and Sharia Financing are financial institutions that are socially based and in their activities are based on moral principles by considering haram and lawfulness of a business that is run in accordance with Islamic regulations. The method used to conduct this research is qualitative. The data source uses secondary data and primary data by collecting data in the form of interviews and documents. Based on the results of observations on KSPPS Berkah Abadi Gemilang that Supervision conducted by DPS there is still an obstacle that causes less optimal supervision, namely members of sharia supervisors who do not understand muamalah fiqh, mastery of economics and DPS rarely make office visits. In addition, one member of the DPS also does not yet have a certificate of proof of passing the exam from DSN-MUI or other standard certificates, in this case at least the results of the certificate provide a guarantee that the Sharia Supervisory Board has passed the feasibility test to become the Sharia Supervisory Board. KSPPS Berkah Abadi Gemilang in practice also still has errors, the Ba'I Bi'saman Ajil contract which is supposed to be a sale and purchase agreement but made as a financing and error in determining the margin based on the presentation of the money lent.